Degradation of endosulfan by a coupled treatments in a batch reactor with three electrodes. (1st December 2020) - Rodriguez-Peña, M.; Barrios, J.A.; Becerril-Bravo, E.; Rodrigo, M.A.; Barrera-Díaz, C.E.
Graphical abstract: Highlights: The integrated process EF/EO/O3 improve the endosulfan removal and decreases the treatment time and energy consumption. The HPLC and TOC confirms the presence of low weight molecular compounds. The EF/EO/O3 process is a sustainable, the electrogeneration of all oxidizing species is a major advantage, due no chemicals are added in the process. The optimal configuration of electrodes was iron (anode) graphite (cathode) and graphite (anode), allow 92% endosulfan degradation efficiency. Graphite electrodes achieve the higher H2 O2 production, having the advantage that this material is cheaper than BDD. Abstract: Endosulfan is one of the most important organochlorine pesticides, due is a persistence, bioaccumulation and toxicity (carcinogenic agent) is important remove this contaminant from wastewater. This work shows the results of the integrated three advanced oxidation process electrofenton/electrooxidation/ozonation (EF/EO/O3 ) to endosulfan degradation. Electrooxidation with Boron doped diamond (BDD) electrodes process achieved 49% of endosulfan degradation efficiency in 2 h, Ozonation process removed 62% in 2 h and electrofenton allows a 72% of endosulfan degradation efficiency. The integrated process EO/O3 improved the removal with 89% in 2 h but the EF/EO/O3 increases the removal to 92% and decreases the treatment time to only 1 h, optimizing the process with a lower energy consumption. The configuration of electrodes that improved de endosulfan degradation was iron (anode), graphite (cathode) and graphite (anode), the graphite electrodes achieved the higher H2 O2 production and this is an advantage to the process, due this material is cheaper than BDD. The electrogeneration insitu of all oxidizing species allow that the process is sustainable.